Co-occurrence of tuberous sclerosis with port wine stain - Rashmi Agarwal; S Suganya; B S Chandrashekar; Sahana M Srinivas (Indian Journal of Paediatric Dermatology, 2021)
Tuberous sclerosis complex is a rare autosomal dominant neurocutaneous disorder characterized by the presence of multiple tumors influencing diverse body frameworks including the central nervous system, skin, eyes, heart, lungs, kidney, and bones. It is described by cutaneous changes, neurologic conditions, and the presence of hamartomas in numerous organs. The treatment of these patients requires a multidisciplinary approach. A port-wine stain is characterized as a telangiectatic macule that manifests during childbirth and stays all throughout life. They are associated with many syndromes. This article reports a rare case of co-occurrence of tuberous sclerosis with port-wine stain in a 2-year-old baby.